2000
DOI: 10.1007/s005340050162
|View full text |Cite
|
Sign up to set email alerts
|

Acinar cell carcinoma of the pancreas showing finger-print-like zymogen granules by electron microscopy: immunohistochemical study

Abstract: A rare case of finger-print-like zymogen granules shown by electron microscopy is reported. The patient was a 75-year-old man who was histologically and ultrastructurally confirmed to have acinar cell carcinoma of the pancreas. Frozen section and postmortem examination revealed that the tumor was made up of solid nests of cells resembling the appearance of normal pancreatic acini, showing polygonal cells which had round or oval nuclei, and rare mitotic figures. Zymogen-like granules, shown by eosinophilic gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The immunohistochemical study from the general endocrine markers chromogranin and synaptophysin, and the pancreatic exocrine enzyme markers trypsin and chymotrypsin is absolutely essential for the correct diagnosis in some cases. [9] Identification of finger‐print‐like zymogen granules by electron microscopy may be helpful in the differential diagnosis [7]. ACCs are negative or focally positive for endocrine markers such as synaptophysin, insulin, glucagons, and serotonin [4, 5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunohistochemical study from the general endocrine markers chromogranin and synaptophysin, and the pancreatic exocrine enzyme markers trypsin and chymotrypsin is absolutely essential for the correct diagnosis in some cases. [9] Identification of finger‐print‐like zymogen granules by electron microscopy may be helpful in the differential diagnosis [7]. ACCs are negative or focally positive for endocrine markers such as synaptophysin, insulin, glucagons, and serotonin [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of ACC is mainly based on histological features such as acinar arrangement, ultrastructural demonstration of zymogen granules, immunostaining for exocrine pancreatic products (trypsin, chymotrypsin, lipase, phospholipase A2, and pancreatic stone protein), and occasional secretion of lipase into the serum [1, ]. Histologically, ACCs are sometimes difficult to differentiate from well‐differentiated endocrine tumors, especially those with a solid and partly trabecular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…6 Toyota et al 13 reported that finger-print-like zymogen granules detected by electron microscopy could be an important factor in the genesis of ACC. 13 Resection is usually selected for the treatment of ACC. An unresected patient has poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Large electron‐dense granules are identified in the tumor by electron microscopy, and neuroendocrine secretory granules may also be found 6. Toyota et al13 reported that finger‐print‐like zymogen granules detected by electron microscopy could be an important factor in the genesis of ACC 13…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of these structures is not clear, although they resemble the earliest zymogen granules encountered in the developing fetal pancreas [57] . Toyota et al [58] indicated that finger-print-like zymogen granules detected by electron microscopy could be an important factor in the genesis of ACC.…”
Section: Electron Microscopic Featuresmentioning
confidence: 98%